PENGARUH PENGENDALIAN INTERNAL DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI YANG DIMODERASI OLEH MORALITAS INDIVIDU (STUDI EMPIRIS PADA PERGURUAN TINGGI DI PROVINSI RIAU) - Fitr Yani; M. Rasuli; Hardi Hardi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
This study aims to examine and analyze the effect of Internal Control andAdherence Accounting Rules Against Fraud Trends in Accounting, IndividualMorality Effect strengthening / weakening of Internal Control and AdherenceAccounting Rules Against Fraud Trends in Accounting. The population of thisresearch is Echelon III and IV and Equivalent Officials Echelon III and IVCollege in Riau Province by the number of samples in this study were 80respondents. Interaction test conducted to test the moderating variables in theform of individual morality by using Moderated Regression Analysis (MRA).The results showed that (1) Internal Control significantly influence the FraudAccounting Trends (2) Adherence Accounting Rules significant effect on theFraud Accounting Trends (3) Individual Morality strengthen internal control tothe Fraud Accounting Trends (4) Individual Morality strengthen AdherenceAccounting Rules to the Fraud Accounting Trends.